2001
DOI: 10.1073/pnas.98.3.1113
|View full text |Cite
|
Sign up to set email alerts
|

Fitness effects of advantageous mutations in evolving Escherichia coli populations

Abstract: The central role of beneficial mutations for adaptive processes in natural populations is well established. Thus, there has been a long-standing interest to study the nature of beneficial mutations. Their low frequency, however, has made this class of mutations almost inaccessible for systematic studies. In the absence of experimental data, the distribution of the fitness effects of beneficial mutations was assumed to resemble that of deleterious mutations. For an experimental proof of this assumption, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
191
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(204 citation statements)
references
References 26 publications
7
191
6
Order By: Relevance
“…For instance, in [108], the distribution of the fitness conferred in the first step was measured in E. coli, which supports the above observation of the occurrence of few mutations with large benefits and many with small payoffs. Similar experiments have also been performed on the RNA virus φ 6 [109].…”
Section: Dynamics Of Microbial Evolutionsupporting
confidence: 58%
“…For instance, in [108], the distribution of the fitness conferred in the first step was measured in E. coli, which supports the above observation of the occurrence of few mutations with large benefits and many with small payoffs. Similar experiments have also been performed on the RNA virus φ 6 [109].…”
Section: Dynamics Of Microbial Evolutionsupporting
confidence: 58%
“…There has been recent empirical evidence (Imhof and Schlotterer 2001;Rozen, de Visser, and Gerrish 2002;Lenski, Rose, Simpson, and Tadler 1991;Sanjuan, Moya, and Elena 2004;Nilsson, Kugelberg, Berg, and Anderson 2004;Joseph and Hall 2004) that rates of adaptive mutations are much higher than previously proposed (Kimura 1983). For example, very recently, evolution experiments of adaptation of the bacterium Salmonella typhimurium to mice have suggested that the adaptive mutation rate for that bacterium can be higher than 10 −6 /cell/generation (Nilsson, Kugelberg, Berg, and Anderson 2004).…”
Section: Discussionmentioning
confidence: 94%
“…He showed that, for a large random mating sexual population, the probability of fixation of a newly arising beneficial mutation is only twice its selective advantage. This means that for mutations that increase fitness of only a few percent (as seems to be the case, (Imhof and Schlotterer 2001;Rozen, de Visser, and Gerrish 2002;Lenski, Rose, Simpson, and Tadler 1991;Sanjuan, Moya, and Elena 2004)) there is more than ninety percent chance that they get lost soon after their appearance. Due to the Hill-Robertson effect (Hill and Robertson 1966), asexual organisms or non-recombining regions of sexual organisms, such as mitochondria and the Y chromosome, suffer from an even smaller probability of fixing adaptive mutations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a basic prediction is that adaptation involves more substitutions in gradually changing environments than under constant selection. The number of substitutions might be estimated from DNA sequence data or by marker-based approaches as in Imhof and Schlö tterer (2001). Furthermore, a hallmark of the moving optimum scenario is a reversal of fitness effects over time (i.e., selection favors first small and then large mutations).…”
Section: Discussionmentioning
confidence: 99%